Ensuring ethical maternal care: addressing episiotomy trends in Pakistan - Shahid, Manal; Niazi, Muhammad Adan Zaman Khan; Bajwa, Alishba (Journal of the Pakistan Medical Association, 2024)
Madam, The use of routine episiotomies, particularly those performed without consent, is a concerning and escalating trend during childbirth in Pakistan. An Episiotomy is a surgical incision in the pelvic floor to enlarge the vaginal opening during labour. The incision is performed under local anaesthetic with scissors. It is deemed necessary only under certain conditions: abnormal progression of labour, suspected foetal distress, vacuum or forceps childbirth, and shoulder dystocia.1,2 Despite the WHO’s recommendation of an episiotomy rate of less than 10% to be considered safe, the rates are disproportionately high in Pakistan. This prompts the need for improved maternal care that is responsible, accountable, and consensual.3 The need for respectful maternal care is crucial in Pakistan. A study conducted in Rawalpindi analysed data from 124798 deliveries and found an 80% incidence of routine episiotomies during normal vaginal deliveries in primigravida cases.3 Another cross-sectional study conducted in Karimabad on 235 patients, also revealed an alarming prevalence of episiotomies, with a rate of 78%.4 These rates differ significantly from those of other countries, such as 17% in New Zealand and 36.5% in Norway, underscoring the potential overuse of episiotomies beyond medical need in Pakistan. Cultural beliefs and a lack of adequately trained staff likely exacerbate this disparity.2,3 Furthermore, increasing episiotomy rates can adversely impact emotional well-being, cause perineal trauma, difficulty in breastfeeding, infection, and delayed healing.2 The intensity of these impacts and the high incidence of episiotomy highlight the need for comprehensive reforms in maternal care practices to ensure the safety and well-being of women. To address this issue, it is imperative to adopt a multifaceted approach that prioritizes informed consent and aims to curb the increasing trend of episiotomies. A commonly presumed benefit of an episiotomy is the prevention of advanced tears; yet, a randomized control trial on 676 patients found no association between decreased use of episiotomy and significant prevalence of severe tears.5 This stresses the need to shift to a policy of selective episiotomies like that implemented in Vietnam. The approach encompasses allocating a budget for routine training of staff, regularly recording rates of episiotomy/tears and including updated guidance about the use of episiotomies within the curriculum.2 Furthermore, when performing an episiotomy patients must be fully informed and individually consented, written or verbal. Opt-out consent may apply in emergencies.1 Such interventions can help ensure higher maternal care standards within Pakistan.